Emerging Perspectives on Dipeptide Repeat Proteins in C9ORF72 ALS/FTD - Schmitz, Alexander; Pinheiro Marques, João; Oertig, Irina; Maharjan, Niran; Saxena, Smita (Frontiers in Cellular Neuroscience, 2021)
The most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) is a hexanucleotide expansion in the gene of chromosome 9 open reading frame 72 (C9ORF72). This hexanucleotide expansion consists of GGGGCC (G4C2) repeats that have been implicated in three main modes of disease pathology: loss of function of the C9ORF72 protein, the generation of RNA foci, and the production of dipeptide repeat proteins (DPRs) through repeat-associated non-AUG (RAN) translation. Five different DPRs are currently known to be formed: glycine-alanine (GA), glycine-arginine (GR) from the sense RNA strand, proline-alanine (PA), proline-arginine (PR) from the antisense strand, and glycine-proline (GP) from both strands. The exact contribution of each DPR to disease pathology is currently under intense scrutiny and is still poorly understood. However, recent advances in both neuropathological and cellular studies have provided us with clues enabling us to understand individual DPR-associated pathology. In this review, we compile the current knowledge of specific DPR involvement on disease development and highlight recent advances, such as the correlation of poly-GR with neurodegeneration, and the possible involvement of chimeric DPR species. Further, the novel nucleolar involvement of arginine-rich DPRs (R-DPRs) on nucleolar protein quality control and the discovery of RAN translation modulators and subsequent promising therapeutic options are also discussed.